Adjuvant radiotherapy improves overall survival in patients with resected gastric adenocarcinoma: A National Cancer Data Base analysis. Issue 17 (17th May 2017) - Stumpf, Priscilla K.; Amini, Arya; Jones, Bernard L.; Koshy, Matthew; Sher, David J.; Lieu, Christopher H.; Schefter, Tracey E.; Goodman, Karyn A.; Rusthoven, Chad G.
Abstract : BACKGROUND: For patients with resectable gastric adenocarcinoma, perioperative chemotherapy and adjuvant chemoradiotherapy (CRT) are considered standard options. In the current study, the authors used the National Cancer Data Base to compare overall survival (OS) between these regimens. METHODS: Patients who underwent gastrectomy for nonmetastatic gastric adenocarcinoma from 2004 through 2012 were divided into those treated with perioperative chemotherapy without RT versus those treated with adjuvant CRT. Survival was estimated and compared using univariate and multivariate models adjusted for patient and tumor characteristics, surgical margin status, and the number of lymph nodes examined. Subset analyses were performed for factors chosen a priori, and potential interactions between treatment and covariates were assessed. RESULTS: A total of 3656 eligible patients were identified, 52% of whom underwent perioperative chemotherapy and 48% of whom received postoperative CRT. The median follow‐up was 47 months, and the median age of the patients was 62 years. Analysis of the entire cohort demonstrated improved OS with adjuvant RT on both univariate (median of 51 months vs 42 months; P = .013) and multivariate (hazard ratio, 0.874; 95% confidence interval, 0.790‐0.967 [ P = .009]) analyses. Propensity score‐matched analysis also demonstrated improved OS with adjuvant RT (median of 49 months vs 39 months; P = .033). On subset analysis, a significant interaction was observed between the survival impact of adjuvant RT and surgical margins, with a greater benefit of RT noted among patients with surgical margin‐positive disease (hazard ratio with RT: 0.650 vs 0.952; P for interaction <.001). CONCLUSIONS: In this National Cancer Data Base analysis, the use of adjuvant RT in addition to chemotherapy was associated with a significant OS advantage for patients with resected gastric cancer. The survival advantage observed with adjuvant CRT was most pronounced among patients with positive surgical margins. Cancer 2017;123:3402‐9 . © 2017 American Cancer Society . Abstract : Based on analysis of the National Cancer Data Base, the use of adjuvant radiotherapy in addition to chemotherapy appears to be associated with a significant overall survival advantage among patients with resected gastric cancer. The survival advantage observed with adjuvant chemoradiotherapy is most pronounced among patients with positive surgical margins.